Current Status and Future Perspective on Lithium Metal Anode Production Methods. Issue 13 (15th February 2023) - Acebedo, Begoña; Morant‐Miñana, Maria C.; Gonzalo, Elena; Ruiz de Larramendi, Idoia; Villaverde, Aitor; Rikarte, Jokin; Fallarino, Lorenzo
Abstract: Lithium metal batteries (LMBs) are one of the most promising energy storage technologies that would overcome the limitations of current Li‐ion batteries, based on their low density (0.534 g cm −3 ), low reduction potential (−3.04 V vs Standard Hydrogen Electrode) as well as their high theoretical capacities (3860 mAh g −1 and 2061 mAh cm −3 ). The overall cell mass and volume would be reduced while both gravimetric and volumetric energy densities would be greatly improved. Their electrochemical performance, however, is hampered by the low efficiency at high current densities and continuous degradation, which are related, among other factors, to the properties of the lithium metal anode (LMA). Hence, the production and processing of LMAs is crucial to obtain the desired properties that would enable LMBs. Here, the conventional method used for the production of LMAs, which is the combination of extraction, electrowinning, extrusion, and rolling processes, is reviewed. Then, the advances in the different alternative methods that can be used to produce and improve the properties of LMAs are described, which are divided into vapor phase, liquid phase, and electrodeposition. Within this last method, the anode‐less concept, for which different approaches to the development of advanced current collectors are illustrated, is included. Abstract : Lithium metal batteries (LMBs) are one of the most promising energy storage technologies that would overcome the limitations of current Li‐ion batteries. Their electrochemical performance, however, is hampered by the continuous degradation of the lithium metal anode (LMA). Hence, the production and processing of LMAs is crucial to obtain the desired properties that would enable LMBs.